2010
DOI: 10.1051/0004-6361/200913331
|View full text |Cite
|
Sign up to set email alerts
|

A wide angle view of the Sagittarius dwarf spheroidal galaxy

Abstract: Context. The Sagittarius dwarf Spheroidal Galaxy (Sgr dSph) provides us with a unique possibility of studying a dwarf galaxy merging event while still in progress. Moving along a short-period, quasi-polar orbit in the Milky Way Halo, Sgr dSph is being tidally dispersed along a huge stellar stream. Due to its low distance (25 kpc), the main body of Sgr dSph covers a vast area in the sky (roughly 15 × 7 degrees). Available photometric and spectroscopic studies have concentrated either on the central part of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 67 publications
(71 reference statements)
3
37
0
Order By: Relevance
“…Thus, we find that the standard error Δv H in a single velocity measurement based on H β fitting is equal to 15 ± 0.5 km s −1 . A similar accuracy of velocity measurements from VIMOS spectra (10-20 km s −1 ) was reported by Giuffrida et al (2010). A quantitatively similar, but intuitive rather than rigorous estimate of Δv H follows from Fig.…”
Section: Discussion Of Errorssupporting
confidence: 85%
See 1 more Smart Citation
“…Thus, we find that the standard error Δv H in a single velocity measurement based on H β fitting is equal to 15 ± 0.5 km s −1 . A similar accuracy of velocity measurements from VIMOS spectra (10-20 km s −1 ) was reported by Giuffrida et al (2010). A quantitatively similar, but intuitive rather than rigorous estimate of Δv H follows from Fig.…”
Section: Discussion Of Errorssupporting
confidence: 85%
“…Typical VIMOS spectra can be calibrated automatically by the ESO-VIMOS pipeline, which cannot, however, be entirely trusted because the spectra of some slits extend below λ = 5000 Å, where calibration lamp lines are scarce 1 , and some of them are very weak. Giuffrida et al (2010) wrote an interactive procedure within the pipeline that provided more control of each calibration step; we decided to reduce the data manually, using standard IRAF 2 procedures. We started from sci_raw frames and proceeded through object identification, slit extraction, flatfielding, science aperture extraction, lamp aperture extraction, wavelength calibration, and normalization of the spectra.…”
Section: Observations and Data Reductionmentioning
confidence: 99%
“…The best colour-magnitude diagrams of Sgr indeed show that multiple, young and intermediate-age populations exist in this galaxy with different metallicities (e.g. Siegel et al 2007;Giuffrida et al 2010). However, the Sgr histogram numbers are small.…”
Section: Discussionmentioning
confidence: 73%
“…Deep Hubble observations (Siegel et al 2006) have revealed an amazing array of stellar populations of various ages and abundances. Similarly, Giuffrida et al (2010) have detected several populations of different metallicities and presumably ages in a few fields in Sgr. According to Bellazzini et al (2006) the mean age of the population in the central region of Sgr is larger than 5 Gyr with a best estimate of 8 ± 1.5 Gyr.…”
Section: Period Distributionsmentioning
confidence: 82%
“…The fit yields a distance modulus of 17.01 (25.2 kpc), a value in reasonable agreement with the currently accepted distance for Sgr. Hundreds of giants in the direction of Sgr have published radial velocities; however, large programs such as the one of Frinchaboy et al (2012) or Giuffrida et al (2010) target K and M giants. Very few C stars have radial velocities to confirm their Sgr membership.…”
Section: Pl Relation and Distancesmentioning
confidence: 99%